DESKRIPSI MINAT BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA PADA MASA COVID-19 KELAS IV - Charla, Ester Elvira; Hamdani, Hamdani; Suparjan, Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe students' interest in learning mathematics in the Covid-19 period, grade fourth at SDN 33 in Bernayau, Sepauk sub-district, Sintang district. The method used in this research is descriptive quantitative method. The object of this research is students' interest in learning. The data sources of this research were all fourth grade students of State Elementary School 33 Bernayau, totaling 25 students. The subject is 5 students. This study used the instruments of observation, interviews and documentation. The results of this study indicate that students' interest in learning in mathematics can be said to be less good, it can be seen from the lack of attention, interest and involvement of students. In addition, the inhibiting factors for students' interest in learning are not good, namely inadequate facilities, less learning media, and less innovative and creative learning methods from the teacher.